PERANCANGAN BALOK BAJA KOMPOSIT GEDUNG KOPERASI DI POLITEKNIK NEGERI BANDUNG - iim, husnul khotimah (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
The Cooperative Building Design at the State Polytechnic of Bandung uses ETABS with composite steel construction. The earthquake analysis method used based on SNI-03-1726-2012 article 7.7.2 is static equivalent because the building is classified as category II and the height does not exceed three floors. Based on the value of SDS = 0.87 and SD1 = 0.777 with the results of type D, it is in accordance with article 7.2.2 earthquake force bearer frame system that is allowed to use a special moment bearer frame. The ratio capacity of the main beam obtained is 0.81. Keywords: composite, cooperative building, equivalent static, special moment bearer frame